Investigation of the absorption of resveratrol oligomers in the Caco-2 cellular model of intestinal absorption. (15th January 2015) - Willenberg, Ina; Michael, Maria; Wonik, Jasmin; Bartel, Laura C.; Empl, Michael T.; Schebb, Nils Helge
Highlights: Resveratrol crosses the Caco-2 cell monolayer and is extensively metabolised. The oligomers ε-viniferin and hopeaphenol do not pass the Caco-2 cell monolayer. A significant portion of the oligomers were detected in the cells. Being not systemically available, the oligomers might act on intestinal epithelium. Abstract: Resveratrol oligomers are biologically active polyphenols found in wine. No information about the bioavailability of these polyphenols is available. In order to discover if the resveratrol oligomers can pass the intestinal barrier, transport of the dimer ε-viniferin and the tetramer hopeaphenol was studied in the Caco-2 transwell system. A flux through the cell monolayer could neither be observed for ε-viniferin nor for hopeaphenol (apparent permeability coefficient ( P app ) < 1 × 10 −6  cm s −1 ). In contrast, resveratrol showed a P app of 11.9 × 10 −6  cm s −1 . Nevertheless, about 16–30% of the oligomers were found in the lysed cellular fraction. This leads to the conclusion that the intestinal absorption rate of the two resveratrol oligomers, ε-viniferin and hopeaphenol, is low and negligible when compared to resveratrol. Therefore, it is unlikely that the oligomers could elicit a systemic biological effect after dietary intake. However, the compounds may act locally on the intestinal epithelium.